Analisis Performance Thresher Pada Stasiun Penebahan Dengan Metode Overall Equipment Effectiveness (OEE) Dan 5S (Studi Kasus:PT.Tri Bakti Sarimas - Keno Widodo; Anita Susilawati; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The Overall Equipment Effectiveness (OEE) is one of the methods of maintenance activities, which aim to preserve and maintain the quality of the equipment or machinery. This research aims to analyze the performance of thresher machine using OEE method (case study: threshing station in PT.Tri Bakti Sarimas). Thresher is used to separate the cook fruitless from bunches. The research was carried out on one thresher unit in PT. Tri Bakti Sarimas, which engaged in palm oil processing industry that produces crude palm oil and kernel. The research method used the Total Productive Maintenance (TPM) approach to analyze the value of OEE and 5S. Analysis over a period of one month and grouped by five days were obtained the OEE value for period of 1-5 April of 72.50%, 6-10 April of 62.22%, 11-15 April of 69.17%, 16-20 April of 57.92%, 21-25 April of 46.60% and 26-30 April of 59.17%. The OEE value of the thresher machine was still belowed the standard OEE word class, which was over 85 %. The main cause of the low OEE values of the thresher machine was compared word class value due to requiring a time for the repair and maintenance processes. Then the idling and minor stoppage losses and set up/adjustment losses factors of the six big losses contributed significantly in lowering the OEE, an average percentage was 48.23 % and 43.06 % respectively. For 5S the problems that occur at the station were mostly found on the condition of the production floor that was dirty, un-tidy, and un-organizer. Therefore, the thresher machine electiveness and productivity may improve by adoption the TPM and 5S methods in the company case study.Keywords: OEE, SixBig Losses, 5S, Thresher